LITURGIA E ECOLOGIA: APONTAMENTOS PARA UMA PRÁXIS PASTORAL ECOLITÚRGICA NA IGREJA METODISTA. - Machado, Leônidas da Cruz (2010)
This research proposes to examine the ecological and pastoral liturgy praxis in the Methodist Church. Praxis is the reflexive activity and the material of the human being. It is a transforming action from an ecological and pastoral in the public dimension of faith. It consists in the study of relationship that should exist between Liturgy and Ecology, and how the praxis can influence and articulate the development of an eco-liturgy, taking as reference the area of Methodist Church. The research is developed in three stages: At first, the theoretical concepts of liturgy, its history, changes and experiences of the human being in the celebrations linked to the elements of nature; second, the concepts of ecology, its crisis and its interrelations to the whole; third, the notes for a pastoral eco-liturgical praxis in the Methodist Church as a reference to create actions that raise awarenes, mobilize for the re-enchantment of spirituality, meaning of life and ecology, to produce hope in the face of social causes that relate to the whole life of human beings. The result will be a set of historical and theoretical references able to deconstruct, construct and reconstruct, in order to sustain a pastoral eco-liturgical praxis. Aiming to achieve a new hermeneutics of the subject, in that gives hope, and a new paradigm of God s reality questions in creation, in the society and the liturgical praxis of the church, in view of the public dimension of faith. The necessity that the human being has to be re-enchanted, recognized, learn to take care, to rebuild all that guarantees the possibility of life and sustainability on the planet.